Tongue-Tie Assessment and Division: A Time-Critical Intervention to Optimise Breastfeeding - Donati-Bourne, Jack; Batool, Zainab; Hendrickse, Charles; Bowley, Douglas M (Journal of Neonatal Surgery, 2015)
Objectives: Recent reports have highlighted the benefits of surgical division of tongue-tie (frenulotomy) in infants with breastfeeding difficulties. There is no clear consensus defining the appropriate age for this procedure to be undertaken in selected infants. We aimed to evaluate the impact of delays in time between referral and frenulotomy in relation to maternal abandonment of breastfeeding. Materials and Methods: This was a prospective cohort study done in out-patient Neonatal Surgery Department, Birmingham Heartlands Hospital, Birmingham, UK, between April 2013 and July 2013. All infants, referred to our tongue-tie clinic between April and July 2013, were studied prospectively. Referral time lags were calculated using computer records; details regarding breastfeeding were collected by an independent interviewer completing a questionnaire. Results: Seventy patients were included. The median infant age at clinic was 28.5 days [range 1-126]. Fifty eight [82%] of mothers had breastfeeding difficulty and their infants were confirmed to have a prominent tongue-tie. By the time of their clinic attendance, breastfeeding had either not been established or abandoned in 21%. Despite difficulty, 61% of mothers persisted breastfeeding and all these mothers consented for frenulotomy. At time of clinic, median age of infants whose mothers had abandoned breastfeeding was 37 days [range 1-80] compared to 27 days [range 1-126] in infants whose mothers had persisted. Conclusions: We demonstrated a time-critical dimension for frenulotomy: delay beyond 4-weeks from referral to assessment of neonatal tongue-tie is more likely to be associated with abandonment of breastfeeding. Timely assessment and division of tongue-tie in selected infants can therefore play an important role in a birthing unit’s breastfeeding strategy.